MANUFACTURING INDUSTRIAL POLICY DEVELOPMENT POLICY FOR ELECTRIC PROPULSION TO IMPROVE LOCAL CONTENT OF RAILWAY INDUSTRY - Utomo, Setyo Margo; Krisnowo, Agus (Deputi TIRBR-BPPT, 2020)
To fulfill the demand for a number of railroad products, the national railroad industry, in this case PT. INKA as a train integrator industry in Indonesia still has to import components. TKDN electric train is still low. For this reason, it is time to prepare the industrial development of the national railway propulsion system components and even have a very urgent nature. Railway propulsion systems can be classified into three groups, namely: Electric propulsion systems, Diesel Electric propulsion systems and Diesel Hydraulic propulsion systems. Import dependence, of course, cannot be allowed to continue because it will weaken the competitiveness of the national railroad industry. From the results of the analysis using the